A novel SERS sensor for the ultrasensitive detection of kanamycin based on a Zn-doped carbon quantum dot catalytic switch controlled by nucleic acid aptamer and size-controlled gold nanorods. (15th November 2021) - Wang, Ximo; Chen, Chen; Waterhouse, Geoffrey I.N.; Qiao, Xuguang; Xu, Zhixiang
Graphical abstract: Highlights: A doubly-enhanced signal SERS sensor was developed for the ultrasensitive detection of kanamycin. Gold nanorods with a longitudinal SPR at 785 nm served as the SERS substrate. A catalytic reaction controlled by a nucleic acid aptamer boosted the SERS signal. The sensor allowed kanamycin quantification over a wide linear concentration range. Abstract: In this study, a novel surface enhanced Raman spectroscopy (SERS) sensor was developed for the ultrasensitive determination of kanamycin in foods. The sensor used two distinct signal amplification strategies, namely the surface plasmon resonance of gold nanorods and a Zn-doped carbon quantum dots catalytic cascade oxidation-reduction reaction switch controlled by a nucleic acid aptamer. Under optimized experimental conditions, the SERS sensor demonstrated a linear range of 10 −12 to 10 −5 g mL −1 for the detection of kanamycin, with a limit of detection of 3.03 × 10 −13 g mL −1 . Experiments with antibiotics structurally similar to kanamycin and interferrants revealed that the sensor had excellent selectivity. Milk powder and honey samples spiked with kanamycin were assayed, with recoveries ranging from 84.1% to 107.2% and a relative standard deviation of 0.74% to 2.81% being obtained. Quantification of kanamycin in milk samples revealed no significant difference between the results obtained with the sensor and by HPLC.